Mandarin Word Order: Syntactic Typology - Brahmana, Reja Aprilla; Mulyadi; Widayati, Dwi (Universitas Cokroaminoto Palopo, 2023)
This research is entitled Tataurut Kata Bahasa Mandarin:Tipologi Sintaksis. The theory used to examine the linguistic phenomena of Mandarin in this study includes two theories, namely the word order typology theory by Greenberg and the theory of relational grammar by Comrie. The research data consisted of Mandarin phrases, clauses, and sentences obtained from the Xunbao newspaper and Mandarin books. The research method used is a qualitative. The results of this study are presented using a formal method. Based on the formulation of the problem and research objectives, the results of the study show that the order pattern of Mandarin word order is SPO/SVO. As for changes in word order patterns, they can turn into SOV because O switches position with V after becoming a passive sentence. The word order pattern in imperative sentences is S-P/S-P-O. Under certain conditions, S can be eliminated but does not change the pattern. Declarative sentences have the S-P/S-P-O pattern. S is to the left of P and cannot precede P. If this occurs, then the pattern is unacceptable. Interrogative sentences have a word order pattern S-P or S-V. Chinese interrogative sentence markers can be located in the middle of a sentence and at the end of a sentence. These markers do not affect the basic pattern of word order, that P always precedes S. S is to the left of P or is praverbal. Through a syntactic typology approach, Mandarin is included in the ergative language type. Mandarin language treats S the same as P (patient) but differently from A (agent).